The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4103/ijt.ijt_75_16
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of microneedling with platelet-rich plasma plus topical minoxidil (5%) and topical minoxidil (5%) alone in androgenetic alopecia

Abstract: Context:There are very few studies evaluating efficacy of platelet-rich plasma (PRP) in hair restoration and its combination with microneedling. As far as ascertained, there is no study to evaluate efficacy of microneedling with PRP plus topical minoxidil (5%) versus topical minoxidil (5%) alone in androgenetic alopecia (AGA).Aims:This study aims (1) to compare the efficacy of (a) topical minoxidil (5%) alone and (b) topical minoxidil (5%) + microneedling with PRP in men between 18 and 50 years with AGA Grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 14 publications
(16 reference statements)
1
68
1
3
Order By: Relevance
“…Moreover, the increase in transepidermal drug delivery is observed for at least 72 hr after the procedure (Lima, Lima, Paixão, & Miot, ). The microtraumatization creates micropores, which results in increased transdermal water loss (Šuca et al, ), however, the result of the study has demonstrated that prompt recovery of skin barrier function is achieved within several hours from device usage (Shah, Shah, Solanki, & Raval, ).…”
Section: Most Commonly Used Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the increase in transepidermal drug delivery is observed for at least 72 hr after the procedure (Lima, Lima, Paixão, & Miot, ). The microtraumatization creates micropores, which results in increased transdermal water loss (Šuca et al, ), however, the result of the study has demonstrated that prompt recovery of skin barrier function is achieved within several hours from device usage (Shah, Shah, Solanki, & Raval, ).…”
Section: Most Commonly Used Devicesmentioning
confidence: 99%
“…Fifty patients were randomly divided into two groups of 25 patients. There was a significant improvement ( p < 0.05) in Group B as compared to Group A. Microneedling with PRP is safe and effective for the management of androgenetic alopecia (Shah et al, ).…”
Section: Main Indications For the Application Of Microneedlingmentioning
confidence: 99%
“…Platelet‐rich plasma was applied one to eight times during a treatment period, which lasted from one to 5 months. Three studies applied co‐interventions (minoxidil, finasteride, or polydeoxyribonucleotide) in addition to PRP in the experimental group and applied the same intervention in the control group without PRP . The rest of 10 studies compared platelet‐rich plasma to placebo (normal saline or distilled water) .…”
Section: Resultsmentioning
confidence: 99%
“…Reference lists were also reviewed to minimize the risk of missing relevant articles. After a comprehensive full‐text review of all articles identified by our search strategy, a total of 15 articles met inclusion and exclusion criteria for analysis . One article reported on and compared 3 preparation methods and was treated as 3 separate studies for the purpose of tabulating study characteristics .…”
Section: Methodsmentioning
confidence: 99%